Middle and modern English corpus linguistics [ a multi-dimensional approach - Markus, Manfred (Studies in corpus linguistics, 2012)
This book brings together a variety of approaches to English corpus linguistics and shows how corpus methodologies can contribute to the linking of diachronic and synchronic studies. The articles in this volume investigate historical changes in the English language as well as specific aspects of Middle and Modern English and, moreover, of English dialects. The contributions also discuss the development of English corpus linguistics generally and its potential in the future. Special focus is given to the continuity between Middle and Modern English - much in line with the linking in previous st